The Impact of COVID-19 Outbreak on Family Planning Services in Indonesia: Evidence from National Routine Statistics - Gayatri, Maria (Universitas Nahdlatul Ulama Surabaya, 2023)
At the beginning of the pandemic, the policy focused on COVID-19 prevention and control. Health facilities faced disruption temporarily regarding contraceptive services. This study analysed the impacts of the COVID-19 outbreak on Family Planning services in Indonesia. Monthly routine statistics from the National Population and Family Planning Board contraceptive service were examined to determine the trends in contraceptive services in Indonesia before and during the COVID-19 Pandemic from January to December 2020. The study was secondary data analysis by utilizing monthly report data from all provinces in Indonesia. Comparison data would account for the monthly trends before and during the pandemic. There was a decrease in contraceptive services between March and April 2020. However, the trend started to increase in June when a one million acceptors campaign was conducted to provide free family planning services in 34 provinces. Injectable (54%) and pills (39%) remain the most favorable contraceptives during the pandemic. IUDs and implants peaked in June 2020 (288,503 users) and September 2020 (214,061 users). The massive campaign of contraceptive services has had a positive impact in increasing the contraceptive users. Contraceptive services are conducted following strict health protocols. Continuation of contraceptive use among reproductive couples still needs to be increased.